Meat mineral content in broilers fed diets without mineral and vitamin supplements - Fuentes Zapata, Jorge Fernando; Saraiva dos Reis Moreira, Regilda; Freire Fuentes, Maria de Fátima; Miranda Sampaio, Eliana; Morgano, Marcelo (Pesquisa Agropecuaria Brasileira, 1998)
A study was conducted to verify the effect of trace mineral and vitamin supplement (MVS) withdrawal from the diet of broilers on meat mineral content. Birds received the following feed treatments: control diet with MVS from day 21 to day 42; diet without MVS from day 21 to day 42; diet without MVS from day 28 to day 42 and diet without MVS from day 35 to day 42. Mineral composition was assessed in light and dark meat from male and female birds. Calcium level was lower in meat from birds fed diet without MVS from day 21 to day 42 as compared to the other treatments. Potassium level was higher in meat from birds fed diet without MVS from day 28 to day 42 than in that from other treatments. Removal of dietary MVS did not affect the meat levels of Na, Fe, Zn and Mn. The meat from female birds showed higher contents of K and Fe than that from male birds. Dark meat was found higher in Ca, Na, Fe and Zn contents and lower in P, Mg and K levels than light meat.
Keywords: light meat; dark meat; poultry nutrition